Child Maltreatment Prevention and Health Promotion: Examining the Effectiveness of a Nurse Home-Visiting Program - Lanier, Paul (2013)
Problem: Child abuse and neglect is a devastating, yet preventable, social problem. Early childhood home visiting services are currently considered the most promising approach to maltreatment prevention. Expansion of evidence-based home visiting services authorized by the Affordable Care Act has created a need to better understand the utilization and effectiveness of preventive services delivered in the community. Nurses for Newborns is a nurse home visiting program serving high-risk caregivers and medically-fragile newborns using a flexible, client-driven service model. Methods: This study used longitudinal services data linked with administrative child welfare data. A sample of low-income families: n = 3,620) who received services from 2009 to 2011 were followed through the end of 2012. Analyses first focused on describing the service population and identifying predictors of engagement and retention. Next, child maltreatment, child development, and maternal mental health outcomes were compared across policy-relevant subgroups. Last, a quasi-experimental design using propensity score analytic methods was conducted to identify a causal treatment effect for maltreatment prevention. Results: The program serves a very high-risk population with individuals experiencing multiple social stressors in addition to medical issues relating to the pregnancy or newborn. There is variation in the level of service use, but generally higher risk families are more likely to engage and participate in services longer. Subgroups of families were found to have higher rates of child developmental concerns, caregiver stress, postpartum depression, and later maltreatment. Families who enroll prenatally appear to be a very different group in terms of risk factors and maltreatment outcomes. Only 1% of families who enroll prenatally have a later maltreatment report compared to 19% of those who begin postpartum. Among postpartum families, propensity score matching was successful in balancing an engaged treatment group with a dropout comparison group. There was not a significant difference between these groups in risk for later maltreatment report. Among families with a maltreatment report prior to home visiting services, the risk of maltreatment was significantly lower for those in the treatment group. Conclusion: Consistent with prior home visiting research, this study found troubling levels of attrition and was not able to detect a statistically significant difference in overall risk of later maltreatment report. Families who receive services prenatally have an exceptionally low rate of later report despite high levels of risk. The program was successful in preventing maltreatment recurrence among those families with a prior report. While some programs serve only first-time mothers, this study found that multiparous clients had some of the highest levels of risk and the poorest outcomes. Lack of overall program findings may be at least partially attributable to low service dosage. This study indicates that NFN is making a measureable impact in maltreatment prevention among certain subgroups of families